Analysis of Interlocking Directorship, Diversification of Operations, Geographical Diversification, Bonus Compensation to Earning Management - Hepi Prayudiawan; Shabrina Azzahra (Journal of Islamic Economy and Business (JIsEB), 2024)
This study aims to analyze empirical evidence of the linkage of leadership positions, operational diversification, geographic spread, and bonus compensation in profit management. We analyzed manufacturing companies on the Indonesia Stock Exchange from 2014 to 2018. Purposive sampling method was used in this study. Discretionary accrual proxies are used on profit management variables. The study was analyzed by multiple linear regression. The study found that leadership linkages, operational diversification, and geographic diversification affect revenue management. The bonus has no effect on performance.